25. CURRENT STATUS OF NURSING CARE FOR PATIENTS IN THE INTENSIVE CARE UNIT, THANH HOA PROVINCIAL GENERAL HOSPITAL, 2021 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of nursing care based on feedback from inpatients treated at the Intensive Care Unit of Thanh Hoa Provincial General Hospital in 2021.Subject and method: A cross-sectional descriptive study was conducted on 245 inpatients receiving treatment in the Intensive Care Unit of Thanh Hoa Provincial General Hospital from February to June 2021. A pre-designed patient interview questionnaire, adapted from the study by Quach Chi Dong on evaluating nursing care activities, was utilized.Results: The average age of patients was 59.56 ± 16.13 years. Among them, 65.7% were male, and 43.3% were farmers. A total of 92.7% of patients highly appreciated the psychological and emotional support provided by nurses. The rate at which nurses verified patients' names and ages and provided full explanations before administering medication was 99.6%.Conclusion: According to patient feedback, nursing care met the essential requirements.
Keywords: Nursing care; patient feedback; inpatients.